TUMBUHAN SUMBER PANGAN YANG DIKONSUMSI OLEH MASYARAKAT PADA TEMBAWANG PAK KUNING DI SENGAH TEMILA - Romana, .; Burhanuddin, .; Thamrin, Eddy (Universitas Tanjungpura, 2018)
This research aims to identify the types of food cropsthat are available and used by the community in the forest area of Tembawang Pak Kuning of Pate Bajambu Hamlet in Senakin Village of Sengah Temila Subdistrict of Landak Regency. This researchis expected to provide information about food crops used by the community around the forest area of Tembawang Pak Kuning of Pate Bajambu Hamlet in Senakin Village of Sengah Temila Subdistrict of Landak Regency, as well as serving as the basis for the management and development of the area by the relevant agencies in the efforts of protection, preservation and utilization of food crops in the future. This research used purposive sampling technique or data source sampling technique with certain considerations by requesting information about food crops through interviews, observation and literature studies. Based on the results, the research found as many as 36 types of plants classified into 24 families. Most of the families are Anacardiaceaewith 6 types (16.67%). The parts that are mostly used are the fruit, which amounted 28 species (77.77%). The way of utilizing itis by direct consumption,namely 18 types (50%), the method of processing is by cooking,namely 25 types (70%), the most widely used is from the fruit group, namely 24 species (66.66%), vegetables as many as 9 species (25%), and 21 species (58%) are wild plants.Keywords: food crops, Pate Bejambu hamlet, tembawang forest.